Factors Affecting Workers' Motivation: A Case Study Of Agriculture Extension Agents In Central Aceh Regency, Indonesia - Idhawati, Idhawati (2014)
The agricultural sector in Indonesia has an important role in the nation's economic development. The role of agricultural extension is not just to improve agricultural production but also to improve the welfare of farmers, thus the big and vital role of the agriculture extension agents in the sector. There are many factors that can inhibit and increase the motivation of agriculture extension agents. The purpose of this study was to identify and test those factors that can motivate or those that inhibit the agents in Central Aceh Regency, Indonesia. For the purpose of the study, all the 190 agriculture extension agents were selected as respondents. The study used the OLS method to determine if the number of visits by the agent to the field, as proxy measure of their motivation, is correlated with the demographic factors (age, gender, marital status and education level) of the respondents and the non-demographic factors including training, salary, transportation and supervision. The findings of the study showed that marital status, training, salary and transportation are statistically significant with motivation of the agriculture extension agents, while gender, age, level of education and supervision are statistically insignificant. Given that the value of R2 is about 0.4, this implies that there are other factors not identified that may inhibit or motivate the agricultural extension agents in Central Aceh Regency.